Evaluation of Precision Xceed® for on-site monitoring of blood ß-hydroxybutyric acid and glucose in dairy cows - PANOUSIS (Ν. ΠΑΝΟΥΣΗΣ) N.; KRITSEPI (Μ. ΚΡΙΤΣΕΠΗ) M.; KARAGIANNIS (Ι. ΚΑΡΑΓΙΑΝΝΗΣ) I.; KALAITZAKIS (ΕΜ. ΚΑΛΑΪΤΖΑΚΗΣ) E.; LAFI, E.; BROZOS (Χ. ΜΠΡΟΖΟΣ) Ch. (Journal of the Hellenic Veterinary Medical Society, 2017)
The aim of the study was to evaluate the usefulness of the Precision Xceed® hand-held meter as an on-site method for determining blood ß-hydroxyboutyric acid (BHBA) and glucose concentrations, for the diagnosis of subclinical ketosis in dry and lactating dairy cows. A total of 163 clinically healthy Holstein cows (113 lactating, 8-50 days-in-milk; and 50 dry, 10-40 days pre-partum) from 5 farms located around Thessaloniki region, were blood-sampled once, from the jugular vein of each animal, 5 to 8 hours after the start of morning feeding. BHBA was determined in all 163 cows, whereas glucose only in 114 cows (50 dry and 64 lactating cows). These analyses were performed, for each cow, by both laboratory method (in serum) and Precision Xceed® meter (in whole blood, cowside). Using laboratory serum BHBA concentrations > 1.2 mmol/L as the cut-off point, 11/163 (6.7%) of the tested cows were considered as subclinically ketotic, whereas raising the cut-off to > 1.4 mmol/L, 9/163 (5.5%) cows had subclinical ketosis. All these cows (11 and 9, respectively) were lactating. None of the dry cows had subclinical ketosis at BHBA cut-off of > 1.4 mmol/L. One out of the 50 dry cows (2%) and 15/113 (13.3%) lactating cows sampled were classified as subclinically ketotic when the Precision Xceed® meter was set at BHBA concentrations > 1.2 mmol/L. Overall, mean BHBA and glucose concentrations were not statistically different (P>0.05) between the two methods. Significant positive correlations were found for BHBA (strong correlation: r=0.99; n=163; P<0.01) and glucose (moderate correlation: r=0.63; n=114; P<0.01) concentrations between Precision Xceed® and laboratory results. Precision Xceed® is less accurate for measuring glucose (glucometer) compared to BHBA (ketometer). The low percentage of false positive (<0.6%) and false negative (<4%) indicating that the Precision Xceed® meter is an accurate screening test and its results are highly reliable under field conditions. Precision Xceed® meter was highly sensitive (90.9%) and specific (96.05%) at cut off point of BHBA concentrations > 1.2 mmol/L and it had excellent test agreement for detection of subclinical ketosis when using a threshold of blood BHBA > 1.4 mmol/L.